2005
DOI: 10.1124/dmd.105.003798
|View full text |Cite
|
Sign up to set email alerts
|

Induction of the Multidrug Resistance-Associated Protein Family of Transporters by Chemical Activators of Receptor-Mediated Pathways in Mouse Liver

Abstract: ABSTRACT:The multidrug resistance-associated proteins ( , -3, -4, -6, and -7 mRNA expression. Mrp3 was also induced by two other CAR activators phenobarbital and diallyl sulfide, two PXR ligands, pregnenalone-16␣-carbonitrile and spironolactone, and the PPAR␣ ligands clofibrate, ciprofibrate, and diethylhexylphthalate. The Nrf2 activators (butylated hydroxyanisole, oltipraz, and ethoxyquin) induced Mrp2-6. In conclusion, a variety of mechanisms are suggested for Mrp3 induction, including AhR, CAR, PXR, PPAR␣, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
217
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(226 citation statements)
references
References 48 publications
6
217
1
2
Order By: Relevance
“…However, splitting the data for the different histological subtypes, it became obvious that this difference was only owing to clear-cell carcinomas, but not for non-CCRCC tissue. There is some evidence that xenobiotics may interfere with signaling pathway involved in the activation of P-gp and MRP2 [27][28][29] or lead to an elevated expression via PXR-transactivating elements. 27,30 However, the lower ABCB1 expression of CCRCC tissue or ABCC2 in non-CCRCC could be also the consequence of altered gene regulation or low cell differentiation and not necessarily causative in the genesis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…However, splitting the data for the different histological subtypes, it became obvious that this difference was only owing to clear-cell carcinomas, but not for non-CCRCC tissue. There is some evidence that xenobiotics may interfere with signaling pathway involved in the activation of P-gp and MRP2 [27][28][29] or lead to an elevated expression via PXR-transactivating elements. 27,30 However, the lower ABCB1 expression of CCRCC tissue or ABCC2 in non-CCRCC could be also the consequence of altered gene regulation or low cell differentiation and not necessarily causative in the genesis of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…OPZ and BHA induced Nqo1 more than 3-fold and 6-fold, respectively, in WT mice, but this induction was almost completely attenuated in Nrf2-null mice; this indicated that the treatments were inducing via the Nrf2 pathway, similar to previous observations. 25 OPZ and BHA produced modest increases in Mrp2 mRNA expression, and although the expression tended to be attenuated in Nrf2-null mice, the decrease was not statistically significant (Fig. 5).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from this laboratory 25 has suggested that Nrf2 activation can lead to Mrp up-regulation, and there is further evidence in vitro that Mrp2 may be regulated by Nrf2. 26 The purpose of this study was to determine whether Mrp2, Mrp3, and Mrp4 are induced (1) in the absence of GSH or (2) after a treatment with Nrf2-activating chemicals in 2 mouse models of Nrf2 activation and (3) whether Mrp induction under these conditions is mediated via the Nrf2-transcriptional pathway.…”
mentioning
confidence: 99%
“…Conjugating enzymes, including glutathione S-transferases (GSTs) and UDP-glucuronosyltransferase, facilitate the removal of toxic and carcinogenic chemicals by increasing their solubility and excretion (19,21,28). Transporters, such as multidrug resistance proteins and p-glycoproteins, are important in the uptake and removal of xenobiotics (18,37,51,58).…”
Section: Innovationmentioning
confidence: 99%